Highly efficient adsorption of uranium(vi) from aqueous solution by a novel adsorbent: titanium phosphate nanotubes. Issue 10 (27th September 2018) - Tang, Mengling; Chen, Juan; Wang, Peifang; Wang, Chao; Ao, Yanhui
Abstract : A novel adsorbent (titanium phosphate nanotube) with high performance for U(vi ) adsorption was fabricated through a facile solvothermal method. Abstract : A novel adsorbent, titanium phosphate nanotube, was fabricated through a facile solvothermal method. The adsorbent was characterized by scanning electron microscopy, nitrogen adsorption–desorption isotherms, X-ray diffraction, zeta potential and Fourier-transform infrared spectroscopy in detail. The as-prepared adsorbent exhibited high performance for U(vi ) adsorption from aqueous solution. The influencing factors including pH, temperature, contact time, adsorbent concentration and adsorbate concentration on the U(vi ) adsorption were systematically investigated. The sorption of U(vi ) on the titanium phosphate nanotube agreed with the Langmuir isotherm model and the maximum adsorption capacity was 344 mg g −1, which is relatively higher than most reported materials in recent years. According to kinetic and thermodynamic studies, the adsorption fitted better with a pseudo-second-order model and it was an endothermic and spontaneous process. The U(vi ) adsorption was mostly attributed to electrostatic interaction and surface complexation. In addition, desorption and reusability studies on titanium phosphate nanotubes showed that their adsorption capacity was not significantly decreased after 4 cycles, indicating that they may have a promising potential for industrial removal of radionuclides from aqueous solution.